Asuhan Kebidanan Continuity Of Care Ny.E.S.M Umur 34, Ibu G3P2A0 Tahun di Puskesmas Haliwen Kabupaten Belu – NTT - Kai Buti, Yovita; Veftisia, Vistra (Universitas Ngudi Waluyo, 2024)
Continuous midwifery care (continuity of care), namely providing midwifery care from pregnancy, delivery, postpartum, neonate until the decision to use family planning. This aims to help monitor and detect possible complications that accompany the mother and baby from pregnancy until the mother uses family planning. Midwifery care methods at the Haliwen Community Health Center, Belu Regency - NTT and through home visits by providing counseling according to the mother's needs. The midwifery care provided to Mrs. In Mrs.